IoT smart meter for electricity consumers - Wali-ur- Rahman, Md.; Chowdhury, Shahrukh Sattar; Ahmed, Syed Istiak; Siddique, Simon (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.